Effect of removal of alkali and alkaline earth metals in cornstalk on slagging/fouling and co-combustion characteristics of cornstalk/coal blends for biomass applications. (May 2023) - Zhu, Hongqing; Liao, Qi; Hu, Lintao; Xie, Linhao; Qu, Baolin; Gao, Rongxiang
Abstract: Co-combustion of cornstalk/coal blends is feasible for large-scale renewable energy commercialization. However, alkali and alkaline earth metals (AAEMs) in cornstalks can cause slagging/fouling problems. In this study, the ash micro-characteristics, slagging/fouling indexes, and combustion behavior of cornstalk, coal, cornstalk after pretreatment, and cornstalk/coal blends were investigated using scanning electron microscopy, X-ray diffraction, X-ray fluorescence, and thermogravimetric experiments. The results demonstrate that cornstalk ash is smoother than coal ash. There are few significant differences in the micromorphology and minerals between the coal and blends. Various chemicals were used to remove AAEMs, with the most to the least effective being (i) soaking in hydrochloric acid, (ii) soaking in ammonium acetate ≈ soaking in distilled water, and (iii) untreated. After soaking in hydrochloric acid, the mineral content containing potassium, calcium, and magnesium significantly decreased in cornstalk ash, except for sodium salt. All pretreatments can effectively lower the slagging/fouling indexes of cornstalk ash and blends. Pretreatment to remove AAEMs would restrain volatile release in cornstalk. The blend resists the volatile release of cornstalk but is helpful for the coke combustion of coal. AAEMs can lower some characteristic temperatures but do not increase the combustion rate and combustion characteristic parameters in the co-combustion of blends.